2021
DOI: 10.3389/fimmu.2021.672165
|View full text |Cite
|
Sign up to set email alerts
|

RDUR, a lncRNA, Promotes Innate Antiviral Responses and Provides Feedback Control of NF-κB Activation

Abstract: Influenza A virus (IAV), a highly infectious respiratory pathogen, remains a major threat to global public health. Numerous long non-coding RNAs (lncRNAs) have been shown to be implicated in various cellular processes. Here, we identified a new lncRNA termed RIG-I-dependent IAV-upregulated noncoding RNA (RDUR), which was induced by infections with IAV and several other viruses. Both in vitro and in vivo studies revealed that robust expression of host RDUR induced by IAV was dependent on the RIG-I/NF-κB pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…To determine whether other pattern recognition receptors (PRRs) and signaling molecules are involved in the regulation of circMerTK expression, we employed several cell lines stably expressing short hairpin RNAs (shRNAs) specifically targeting PRRs or signaling molecules, as previously described ( 24 26 ). We observed that knockdown of interferon regulatory factor (IRF) 3, IRF7, and mitochondrial antiviral-signaling protein (MAVS) significantly reduced circMerTK levels following IAV infection, but knockdown of antimelanoma differentiation-associated gene 5 (MDA5) had no significant impact on circMerTK expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether other pattern recognition receptors (PRRs) and signaling molecules are involved in the regulation of circMerTK expression, we employed several cell lines stably expressing short hairpin RNAs (shRNAs) specifically targeting PRRs or signaling molecules, as previously described ( 24 26 ). We observed that knockdown of interferon regulatory factor (IRF) 3, IRF7, and mitochondrial antiviral-signaling protein (MAVS) significantly reduced circMerTK levels following IAV infection, but knockdown of antimelanoma differentiation-associated gene 5 (MDA5) had no significant impact on circMerTK expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several IAV-upregulated lncRNAs have been found to inhibit IAV replication. For example, lnc-ISG20 [ 25 ] and ISR [ 29 ] function as interferon-stimulated genes (ISGs), and LncRNA-155 [ 26 ], NEAT1 [ 39 ], SAAL [ 40 ], RDUR [ 41 ], AVAN [ 42 ] and IVRPIE [ 43 ] can suppress IAV replication by promoting innate immune responses to viral infection. However, it remains unknown how the expression levels of these lncRNAs are regulated and whether RNA modifications play roles in the lncRNA regulation in response to the virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RIG-I-dependent IAV upregulated noncoding RNA (RDUR), induced by Influenza A virus (IAV) infection, can positively regulate the signal transduction of type I interferon (IFN-1) by affecting IRF3 and further upregulates the expression of several vital antiviral molecules. It is concluded that RDUR is a critical regulator of innate immunity against viral infection [ 27 ]. And lncRNA-GM can bind to glutathione S-transferase M1 (GSTM1), block the interaction between GSTM1 and TANK binding kinase 1 (TBK1), and reduce GSTM1-mediated glutathione.…”
Section: Discussionmentioning
confidence: 99%